Pengamatan terhadap Proses Pertumbuhan Tanaman Kangkung di Bawah Variasi Intensitas Cahaya Matahari: Observations on the Growth Process of Kale Plants under Variations in Sunlight Intensity - Humairoh, Azzarina Azka; Prayogo, Muhammad Suwignyo; Sa'adah, Putri Aulia Liliatis; Hasanah, Silvi Nabilatul (Universitas Pahlawan Tuanku Tambusai, 2025)
Sunlight is one of the important factors in the process of plant growth, especially because of its role in photosynthesis. This study aims to visually observe the physical changes of kale (Ipomoea aquatica) plants grown under two different lighting conditions, namely full light and minimal light. The research was conducted qualitatively descriptive with direct observation method on two groups of plants in small pots for 30 days. Aspects observed included leaf color and shape, stem growth direction, and plant freshness. Group A (full light) showed wider and darker green leaf growth, upright stems, and a fresher plant appearance. In contrast, group B (minimum light) showed pale leaves, stems that leaned towards the light source, and a more lethargic plant condition. These results indicate that light intensity affects the visual appearance and direction of plant growth. Light-deprived plants remained viable, but showed signs of stress such as lethargy and phototropism. This study confirms that sufficient light is essential in kale cultivation, not only for optimal yield, but also in terms of plant health and aesthetics. It is recommended that the plants be placed in a place that receives adequate light, and further research can consider other environmental factors such as humidity and temperature.